VD_FINDINFO LAVAM 9/15 - 4/2016 vom 5. Februar 2016 - VD Tribunal cantonal (2016)
PRIME D'ASSURANCE-MALADIE, SUBVENTION, DROIT D'ASILE | 65 LAMal, 82a LAsi, 11 LVLAMal, 12 LVLAMal, 9 LVLAMal, 17 RLVLAMal, 5b OA 2